Energy efficient distillation columns design for retrofit NGLs fractionation process - Mohd Faris, Mustafa; Noor Asma Fazli, Abdul Samad; Kamarul, Asri Ibrahim; Norzana, Ibrahim; Mohd Kamaruddin, Abd Hamid (Trans Tech Publications, Switzerland, 2015)
Distillation is the primary separation process widely used in the industrial chemical process. Although it has many advantages, the main drawback is its large energy requirement, which may significantly influence the overall plant profitability. However, the large energy requirement of these processes can be systematically reduced by using driving force and energy integration methods. This paper presents a methodology for designing energy efficient distillation columns systems based on those two methods. Generally, the proposed methodology consists of four hierarchical steps. In the first step, the system of distillation columns for multicomponent separation is designed based on the conventional distillation column design (shortcut) method. Then, the conventional distillation columns systems design is improved in terms of energy saving by using driving force method in the second step. It is expected in the third step that the distillation columns systems design can be further improved in terms of energy saving by using energy integration method. Finally, the distillation columns systems design is evaluated in terms of economic performance. The simulation results by using Aspen HYSYS have shown that the driving force sequence by using shortcut method for NGLs has energy savings with 55% reduction compared to a direct method with shortcut method. It can be verified that the proposed methodology has the capability in designing energy efficient distillation columns in an easy, systematic and practical manners.